A cost of illness study of hypoglycaemic events in insulin-treated diabetes in the Netherlands. Issue 3 (25th March 2018) - de Groot, Saskia; Enters-Weijnen, Catherine F; Geelhoed-Duijvestijn, Petronella H; Kanters, Tim A
Abstract : Objectives: Patients with diabetes mellitus are at a risk for hypoglycaemia. Besides the burden of hypoglycaemia for patients, hypoglycaemia poses an economic burden to society. The aim of this study was to calculate the per patient societal costs of hypoglycaemia among patients with type1 diabetes (T1DM) and type 2 diabetes (T2DM) on insulin therapy in the Netherlands. Methods: To calculate the costs of hypoglycaemia, data from the Global Hypoglycaemia Assessment Tool (HAT) study were used. Dutch patients were selected from the HAT study database and data regarding healthcare resource use, informal care use and productivity losses were combined with Dutch unit costs to calculate the per patient 4-week costs of patients experiencing hypoglycaemia. Besides these 4-week costs, costs per hypoglycaemic event were calculated by dividing the study population total 4-week costs by the total number of events in this period. Results: Mean 4-week total costs of hypoglycaemia amounted to €163 (SD, €870) in T1DM and €134 (SD, €364) in T2DM. While productivity costs were the most important cost driver of hypoglycaemia in patients with T1DM (accounting for 72% of the total costs), costs of hypoglycaemia in patients with T2DM were almost entirely driven by costs within the healthcare sector (accounting for 98% of the total costs). Mean costs of a severe hypoglycaemic event were €828 and €508 in T1DM and T2DM, respectively, whereas mean costs of a non-severe event were almost zero. Conclusions: This study showed that the economic burden of severe hypoglycaemia is substantial. The prevention of hypoglycaemia could therefore not only reduce the burden for patients, but also the economic burden to society.